Process for authentication of Tinospora cordifolia based herbal supplements - Sarkar, Rohan; Banerjee, Kaushik; Chatterjee, Niladri (Indian Horticulture, 2023)
Tinospora cordifolia based herbal supplements have recently gained prime importance due to their immunomodulatory and anti-viral effects. But mislabelling or diluting the herbal supplements for profit may harm public health. That’s why validating the label claim/authenticity of the supplements available in markets is crucial. This study involves on how high-resolution mass spectrometry (HRMS)-based metabolomics and chemometrics approach can be useful to distinguish Tinospora cordifolia from two other closely related species, i.e. T. crispa and T. sinensis.